The only formulas you have to know are:
![\begin{gathered} √(a\cdot b)=√(a)\cdot√(b) \\ i^2=-1\rightarrow i=√(-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/apare2nwk9heu47rob9v8ossvvlme7ma2z.png)
When you do not know the root of a number, you have to express its root like a product of its main factors, for example:
![√(75)=5√(3)](https://img.qammunity.org/2023/formulas/mathematics/college/ryd92gbevm4hgq4ngd5k49goxvduhdp6nf.png)
To find these factors, we can divide the original number among other numbers and multiply them, for example:
When we know those factors, we can use the laws of roots to simplify:
![\begin{gathered} 75=5^2\cdot3 \\ \sqrt[]{75}=√(5^2\cdot3)=5^{(2)/(2)}\cdot√(3)=5√(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yqoce7wvvfjvmpphcfmujhf1zbt89f6r7g.png)
With this in mind, we can now solve the exercise:
First term:
![\begin{gathered} (-20\pm√(75))/(5) \\ \\ (-20\pm5√(3))/(5)\text{ \lparen Divide each term of the numerator by the denominator\rparen} \\ \\ -4\pm\sqrt[]{3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5m3sznjuvk3oxev2z8uazwi4xeojibpgnu.png)
Second term:
*Notice that
![√(-81)=√((-1)\cdot(81))=√(81)\cdot√(-1)=√(81)i=9i](https://img.qammunity.org/2023/formulas/mathematics/college/1izopa299847objdpyxnga0n8iv05166ne.png)
![\begin{gathered} (6\pm√(-81))/(3) \\ \\ (6\pm9i)/(3) \\ \\ 2\pm3i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/92axu0303jg9bzzc5opmgl1sbhtfb4ugky.png)
Third term:
*Notice the followings:
![√(-28)=√(28\cdot-1)=√(28)\cdot√(-1)=√(4\cdot7)i=2√(7)i](https://img.qammunity.org/2023/formulas/mathematics/college/nla3k9o2r23552sngidwd8xn17gu5i7zdr.png)
Finally,
![\begin{gathered} (-4\pm√(-28))/(8) \\ \\ (-4\pm2√(7)i)/(8) \\ \\ (-4)/(8)\pm(2√(7))/(8)i \\ \\ (-1)/(2)\pm(√(7))/(4)\imaginaryI \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l4txp11zaf8omi0z4bozp7ryn2kdqzei8t.png)